Sensitivity analysis of a morphodynamic modelling system applied to a coastal lagoon inlet - Plecha, S.
This work investigates the recent morphological changes at the inlet of a complex coastal system (Ria de Aveiro lagoon, Portugal). This study was carried out using bathymetric data analysis and numerical simulations obtained with the 2DH morphodynamic modelling system MORSYS2D. The present simulations considered only tidal forcing, and a sensitivity analysis was performed by tuning the formula used to compute the sediment transports. A non-uniform sediment grain size distribution for the Ria de Aveiro inlet is considered in the numerical simulations, based on surveys performed in this area. The model results are analysed to assess if they resemble the observed trends of erosion and deposition, as calculated from bathymetric data. A quantitative analysis of the differences between the bathymetric changes obtained through surveys and the numerical results over a period of 3 years considering different sediment transport formulations shows that the formulations of Ackers and White (1973) and Engelund and Hansen (1967) are the ones that best describe the morphodynamic changes driven by tides in the Ria de Aveiro inlet.